2020
DOI: 10.1002/cctc.201902219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen Bond Donating Sites in UiO‐66 Metal‐Organic Framework for Highly Regioselective Methanolysis of Epoxides

Abstract: A Zr(IV)‐based UiO‐66 metal‐organic framework (MOF) (named 1) was synthesized by employing 1‐(aminomethyl)naphthalene‐2‐ol appended terephthalate linker and Zr(IV) salt via solvothermal method and subsequently characterized. Furthermore, the potential efficiency of activated (named 1′) form of as‐synthesized MOF was investigated as an organocatalyst for the ring‐opening of epoxide by methanol. The catalytic performance of 1 and 1′ was studied in the methanolysis of styrene oxide as a model substrate and the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 65 publications
(156 reference statements)
0
32
0
Order By: Relevance
“…In particular, heterogeneously catalysed synthesis of industrially relevant compounds, such as fine chemicals and pharmaceuticals, through the C-C and C-N bond-forming processes is a recent example where MOFs can bridge state-of-theart homogeneous catalysts with robust reusable solid catalysts. 39,42,43 Herein, we study the effects of the acidity and molecular size of modulators on UiO-66 properties in relation to its catalytic performance in the transformation of epoxides into amino alcohols via MOF-catalysed C-N bond formation, 36,[44][45][46][47] aiming to provide insights that will lead to the design of catalytic MOF systems based on their controlled properties. We have chosen UiO-66, a robust system that allows for precise control of its chemical reactivity through defect engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, heterogeneously catalysed synthesis of industrially relevant compounds, such as fine chemicals and pharmaceuticals, through the C-C and C-N bond-forming processes is a recent example where MOFs can bridge state-of-theart homogeneous catalysts with robust reusable solid catalysts. 39,42,43 Herein, we study the effects of the acidity and molecular size of modulators on UiO-66 properties in relation to its catalytic performance in the transformation of epoxides into amino alcohols via MOF-catalysed C-N bond formation, 36,[44][45][46][47] aiming to provide insights that will lead to the design of catalytic MOF systems based on their controlled properties. We have chosen UiO-66, a robust system that allows for precise control of its chemical reactivity through defect engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be concluded that both IITG-5 and IITG-5a have similar thermal stabilities to that of the other reported UiO-66 family of Zr-MOFs. 34,35 The experimental and theoretical weight losses due to the degradation of the organic linkers were ∼57% and ∼71%, respectively. Such a difference between experimental and theoretical weight losses clearly indicates that there are some linker defects in the MOF structure.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Therefore, the chemical stability of IITG-5a is comparable to other reported UiO-66 types of Zr-MOFs. 34,36 N 2 sorption analysis For the determination of surface area (BET) and pore volume of IITG-5a, the N 2 sorption analysis was performed at a temperature of −196 °C (Fig. S9, ESI †).…”
Section: Chemical Stabilitymentioning
confidence: 99%
“…Although Lewis bases as well show capability toward epoxide hydroxylation (Table 1, entries 11-15; and SI, Section 4), in this work, the coordination environment influenced Lewis-acidity dominates the catalytic activity on the basis of the abovementioned characterization and catalysis results. [46,47] Typically, the Lewis-acidic Zn 2 + -sites could be coordinated with the oxygen atom in the PO ring through an acid-base interaction, which in turn increases the electrophilicity of the neighbored carbon atoms in the epoxide. MeOH then attack the activated carbon atoms through either I or II pathway to give the main product and byproduct (Figure 5).…”
Section: The Proposed Mechanism Toward Epoxide Hydroxylation Reactionsmentioning
confidence: 99%